Comparative Effects of Organic and Inorganic Fertilization with Mycorrhizal Inoculation on the Growth and P-Uptake of Salak (Salacca zalacca) Seedlings in a Compost-Amended Andisol - Anasrullah Anasrullah; Nandariyah Nandariyah; Sri Hartati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The cultivation of salak (Salacca zalacca) on Andisols is constrained by low phosphorus (P) availability due to the soil's high P-fixation capacity. To evaluate strategies for enhancing P uptake, a 180-day greenhouse experiment was conducted using a factorial completely randomized design. Salak seedlings were grown in a compost-amended Andisol (2:1 v/v) and subjected to three fertilizer treatments (control [P0], liquid organic fertilizer [P1], and inorganic NPK [P2]) combined with three dosages of a Glomus-based arbuscular mycorrhizal fungi (AMF) inoculum (0 g [M0], 30 g [M1], and 60 g [M2] polybag⁻¹). The results revealed distinct treatment effects on soil, microbial, and plant parameters. In the soil, the inorganic NPK fertilizer (P2) induced significant acidification (pH 6.17), while the liquid organic fertilizer (P1) maintained a more neutral pH (7.03); however, final soil-available P was not significantly different among treatments. Biologically, the P2 treatment severely suppressed the mean mycorrhizal infection rate to 20.0%, significantly lower than the 53.3% observed under the P1 treatment. These effects directly translated to plant growth, where P1 produced significantly taller plants and greater fresh weight, and the P1M2 combination yielded the longest roots (42.43 cm). Ultimately, these improvements culminated in superior plant nutrition, with the P1 treatment facilitating the highest P uptake (0.145 g/plant), nearly double that of the P2 treatment (0.073 g/plant). The findings systematically demonstrate that an integrated approach using liquid organic fertilizer and AMF inoculation is a superior strategy for enhancing nutrient uptake efficiency and promoting vigorous growth in salak nurseries on P-fixing Andisols